Efficacy of nutritional talks in the prevention of anemia in children (6 to 36 months of age) from a health center in Chiclayo, Peru: Eficacia de charlas nutricionales en la prevención de anemia en niños (6 a 36 meses de edad) de un centro de salud en Chiclayo, Perú - Silva Fiestas, Jorge Enrique (2023)
Introduction: There is a high prevalence of anemia in Peruvian children. Objective: To evaluate the efficacy of nutritional talks at a health center in Chiclayo in reducing and preventing anemia in children from 6 to 36 months of age. Methods: Descriptive cross-sectional study. We studied 78 children cared for in a primary health care center. Information from growth evaluations was extracted from a database generated by the center. We recorded the hemoglobin level (close to the date of the intervention and in subsequent controls ≥1 month later), we also collected information from the participants and care. Results: 41 children (52.57%) participated in the nutritional talk, no significant differences being observed with the group that did not participate. We observed a higher frequency of anemia in the group that did not participate in the nutritional talk (23.03%) with respect to the one that did participate (0%), a significant difference in time was evident between Hb evaluations (p <0.001) and the indication of micronutrients (p <0.001) for both groups. Despite this, there was no significant difference between the initial and final Hb values. The groups with anemia were studied, showing a longer time between evaluations and a lower indication of micronutrients with a significant difference of p <0.001 and p = 0.030 respectively. Conclusion: Children whose parents participated in nutritional talks had less anemia. This suggests that nutritional talks could help prevent anemia. Key words: Anemia, nutrition programs, infant nutrition, infant care